Medsebojna vezanost na odločbe sodišč v civilnih zadevah - Bergant Rakočević, Vesna (Pravni letopis, 2016)
This article tackles the multifaceted question of interdependence of judgments in civil proceedings in view of the desired predictability of judicial decisions. Although it might seem that conformable decisions (or interdependent judgments) in similar civil matters are a necessity and help build the confidence in the judicial system they are in fact the exception, focused on preliminary questions and the so called intervention effect. This interdependence is generally subject to the condition that the party who is to be bound by a decision from another case had had the opportunity to participate in the process of adopting that decision. More frequent are situations where there is no formal linkage although the relevant facts and issues are identical; the influence of a final decision is then limited to the persuasiveness of its arguments, taking into account the possible difference of pleading and proof submitted by the parties. The requirement of conformable decisions (interdependent judgments) may be required by the nature of the substantive relationships in question, although it is sometimes difficult to ensure. Contradictory action of the same party in different cases can be prevented by the proper application of the general principle against the abuse of rights (venire contra factum proprium).
Keywords: civilno pravo; sodne odločbe; sodni postopek